Management Of Spontaneous Pneumothorax In Er Of A Tertiary Care Hospital – An Observational Study. (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: Pneumothorax is an emergency having high mortality rate. Early recognition and  management is crucial. Aim: To study the demographic data, clinical presentation, risk factor and management of  cases of spontaneous pneumothorax presenting to ED. Material and Method: Observational analytical study done in 75 patients aged 20-74 years  admitted at a tertiary care hospital from April 2018 to March 2019. Patients coming with  spontaneous pneumothorx in ER were included in the study. History of trauma and iatrogenic  causes were excluded. Result: Details about demographic data, clinical presentation, risk factor and management were recorded. Their main complaints were dyspnoea followed by chest pain. In our study out  of 75 patients, ICD was inserted in 63 patients,7 patients managed with simple needle  aspiration and 5 patients were treated conservatively. In our study 58 patients were shifted to  E Ward/ICU, 8 patients were shifted to CT Sx ward, 5 patients shifted to ward, 3 patients took LAMA and 1 patient expired. Conclusion: In our study we found that SSP (secondary spontaneous pneumothorax) is more  common than PSP (primary spontaneous pneumothorax) , majority of patients were male and  COPD(chronic obstructive pulmonary diseases) is the commonest cause of the SSP. Intercostal  tube drainage is the main mode of management.
Keywords: Spontaneous pneumothorax; chronic obstructive pulmonary disease; intercostal tube drainage